(untitled) (Eurasian Research Bulletin, 2022)
The Strategy for the Development of the Information Technology Industry in Uzbekistan for 2022-2026 and for the period up to 2030 emphasizes that information and communication technologies contribute to improving the quality of educational services. At the same time, it is noted that a necessary condition for the development of the IT industry is “a high level of knowledge of school and university graduates in mathematics and natural sciences. The decline of this level in recent years is a direct threat to such development.”